Maternal complications and associated factors among mothers who underwent a cesarean section at Gebretsadik Shewa general hospital: an institution based cross-sectional study - Negese, Ketemaw; Belachew, Dereje Zeleke (Frontiers in Global Women's Health, 2023)
Introduction Cesarean sections have played a major role in lowering maternal morbidity and mortality rates, but are a major concern in developing countries. This study aims to assess the magnitude of maternal complication and its associated factors among women who underwent a cesarean section at Gebretsadik Shewa general hospital, Southwest Ethiopia. Method A hospital-based cross-sectional study was conducted in Gebretsadik Shewa general hospital. Data were extracted from 382 mothers' medical charts, retrieved from the labor and operations theatre log book registry using systematic random sampling technique. The extracted data was coded and entered into Epi Data version 3.0, and exported to Statistical Package for Social Sciences (SPSS) version 20 for analysis. Logistic regression analysis was conducted and significance and strength association was determined considering AOR with a 95% confidence level. Result A total of 382 mothers' charts were reviewed; however, 368 charts were eligible for data entry. The age of the participants ranges between 16 and 42 years with mean and standard deviation of 26.1 ± 4.8 years. Maternal complication rate was 30.4% [95% CI: 25.8- 35.1]. Surgical site infection (10.3%), anemia (6.5%) and intraoperative bleeding (4.6%) were the most common. Multivariable logistic regression analysis showed that no antenatal care follow up, medical illness during pregnancy, emergency cesarean section and not receiving a prophylactic antibiotic were statistically associated with maternal complications. Conclusion The incidence of maternal complication following cesarean delivery was unduly high. Community based education about antenatal care follow up and its importance should be further strengthened for favorable maternal and fetal outcomes.